The Development Of A Postgraduate Management System (PG-MS) - Nusir, Muneer Saeed Ahmad (2008)
This study aims to develop a prototype system for postgraduate students in UUM especially students in the Graduate Department of Information Technology, Computer Science and Multimedia, focusing on the entry requirements for the final project. Because of the increasing number of postgraduate students in this department, it usually takes quite a long time to fill the application manually and to do the processing of the application after it has been submitted. The system development life cycle (SDLC) methodology will be used in this study and it considers the general methodology to develop the system.